2014
DOI: 10.1371/journal.pone.0083908
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Ameliorates Inflammation and Fibrosis in the Early Phase of Cirrhotic Portal Hypertension in Rats through Inhibition of mTORC1 but Not mTORC2

Abstract: ObjectiveHepatic stellate cells (HSCs) transdifferentiation and subsequent inflammation are important pathological processes involved in the formation of cirrhotic portal hypertension. This study characterizes the pathogenetic mechanisms leading to cholestatic liver fibrosis and portal hypertension, and focuses on mammalian target of rapamycin (mTOR) pathway as a potential modulator in the early phase of cirrhotic portal hypertension.MethodsEarly cirrhotic portal hypertension was induced by bile duct ligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
2
38
0
1
Order By: Relevance
“…Wang et al . found that inhibition of mTORC1 ameliorated fibrosis in rat model of bile duct ligation 23. Li et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Wang et al . found that inhibition of mTORC1 ameliorated fibrosis in rat model of bile duct ligation 23. Li et al .…”
Section: Discussionmentioning
confidence: 98%
“…Growing researches show that mTOR pathway plays an important role in HSCs activation 22, 23, 24. Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the epithelial-mesenchymal transition (EMT), a major mechanism of tubulointerstitial fibrosis [11,12], is tightly associated with mTOR activity. Rapamycin (Rap), an mTOR signaling inhibitor, exerts an anti-fibrosis effect in many tissue fibrosis diseases [13,14,15]. However, whether Rap exerts a renoprotective effect in Aldo-induced renal injury has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In rats with cirrhotic portal hypertension induced by bile duct ligation, mTOR was markedly activated and treatment with mTOR inhibitors decreased ALT, AST, alkaline phosphatase, intrahepatic neutrophils and lymphocytes and reduced TNF-α and inducible nitric oxide synthase mRNA expression. Moreover, reduction of fibrosis up to 70%, numbers of cholangiocytes and myo fibroblasts, and hepatic extracellular matrix deposition was observed [39,40]. Moreover, in post liver transplant patients, the use of mTOR inhibitors was associated with slower rate of liver fibrosis [41].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between mTOR and inflammation could be mutual where inflammatory cytokines such as TNF-α may activate mTOR [42] and mTOR promotes the expression of pro-inflammatory cytokines like TNF-α, IL-6, IL-1α and IL-1β [35,39,40]. In addition, mTOR activation enhances the expression of monocyte chemotactic protein-l and hepatic macrophage infiltration and polarization with M2 to M1 phenotype switch [43].…”
Section: Discussionmentioning
confidence: 99%